The Source-Study Value of Garegin Nzhdeh’s Works in the Historical and Military-Geographical Studies of Syunik - Ghazaryan, Gor; Danielyan, Samvel (History and Culture, 2026)
General Garegin Nzhdeh’s works contain multifaceted information about the natural environment of Syunik, which is of great significance for the region’s historical and military-geographical studies. This information includes Syunik’s mountains, rivers, climatic conditions, flora and fauna, as well as its topographical features. In this article, the scientific observations found in Nzhdeh’s works have been systematized and analyzed, comparing them with historical sources and contemporary data. Based on this information, it is possible to reconstruct the natural characteristics of Syunik during 1919-1921, including its military-geographical nature, as well as assess the ecological changes that have occurred in the region over time.